Long-term economic evaluation of cognitive-behavioural group treatment versus enhanced usual care for functional somatic syndromes - Schröder, A; Ørnbøl, E; Jensen, J; Sharpe, M; Fink, P (Elsevier, 2017)
Objective: Patients with functional somatic syndromes (FSS) such as fibromyalgia and chronic fatigue syndrome have a poor outcome and can incur high healthcare and societal costs. We aimed to compare the medium-term (16 months) cost-effectiveness and the long-term (40 months) economic outcomes of a bespoke cognitive-behavioural group treatment (STreSS) with that of enhanced usual care (EUC). Methods: We obtained complete data on healthcare and indirect costs (i.e. labour-marked-related and health-related benefits) from public registries for 120 participants from a randomised controlled trial. Costs were calculated as per capita public expenses in 2010 €. QALYs gained were estimated from the SF-6D. We conducted a medium-term cost-effectiveness analysis and a long-term cost-minimization analysis from both a healthcare (i.e. direct cost) and a societal (i.e. total cost) perspective. Results: In the medium term, the probability that STreSS was cost-effective at thresholds of 25,000 to 35,000 € per QALY was 93–95% from a healthcare perspective, but only 50–55% from a societal perspective. In the long term, however, STreSS was associated with increasing savings in indirect costs, mainly due to a greater number of patients self-supporting. When combined with stable long-term reductions in healthcare expenditures, there were total cost savings of 7184 € (95% CI 2271 to 12,096, p = 0.004) during the third year after treatment. Conclusion: STreSS treatment costs an average of 1545 €. This cost was more than offset by subsequent savings in direct and indirect costs. Implementation could both improve patient outcomes and reduce costs.